The power and potential of BIOMAP to elucidate host‐microbiome interplay in skin inflammatory diseases. Issue 10 (24th August 2021) - Alenius, Harri; Sinkko, Hanna; Moitinho‐Silva, Lucas; Rodriguez, Elke; Broderick, Conor; Alexander, Helen; Reiger, Matthias; Hjelmsø, Mathis Hjort; Fyhrquist, Nanna; Olah, Peter; Bryce, Paul; Smith, Catherine; et al.
Abstract: The two most common chronic inflammatory skin diseases are atopic dermatitis (AD) and psoriasis. The underpinnings of the remarkable degree of clinical heterogeneity of AD and psoriasis are poorly understood and, as a consequence, disease onset and progression are unpredictable and the optimal type and time point for intervention are as yet unknown. The BIOMAP project is the first IMI (Innovative Medicines Initiative) project dedicated to investigating the causes and mechanisms of AD and psoriasis and to identify potential biomarkers responsible for the variation in disease outcome. The consortium includes 7 large pharmaceutical companies and 25 non‐industry partners including academia. Since there is mounting evidence supporting an important role for microbial exposures and our microbiota as factors mediating immune polarization and AD and psoriasis pathogenesis, an entire work package is dedicated to the investigation of skin and gut microbiome linked to AD or psoriasis. The large collaborative BIOMAP project will enable the integration of patient cohorts, data and knowledge in unprecedented proportions. The project has a unique opportunity with a potential to bridge and fill the gaps between current problems and solutions. This review highlights the power and potential of the BIOMAP project in the investigation of microbe‐host interplay in AD and psoriasis.